Fuzzy Ideals of Pre A * -Algebras: المثاليات الضبابية في جبور * Pre A (المجلة العربية للعلوم و نشر الأبحاث, 2022)
We’ve introduced in this paper the notion of fuzzy ideals of Pre A * –algebras and investigated of some of their properties. We’ve proved characterization of fuzzy ideals by their level of fuzzy sets. Also, we’ve proved some characterizations of fuzzy ideals generated by a fuzzy set in terms of their level fuzzy sets too. Furthermore, we’ve introduced some theorems related to homomorphism of Pre A * –algebras and images of fuzzy ideals according to them, also some theorems of Cartesian product of fuzzy ideals, and marginal fuzzy set from the Cartesian product of Pre A * –algebras.